Training on Making Simple Basic Fish Feed to Improve the Skills of Fish Farmers Milkfish - Kasi, Yohanes Freadyanus; Lena, Fransiskus Jenga; Sode, Anastasia (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The people of Aeramo village, Nagekeo Regency, who work as fish farmers, find it very difficult to provide fish feed due to the high feed price. The purpose of implementing this community service activity is to provide information about the process of making simple-based fish feed and their response.  Community service was carried out in June 2023 in Dusun II, Aeramo Village, Nagekeo Regency. The activity method is Asset Based Community Development (ABCD), which aims to carry out community service based on the strengths and potential of the community. Discussions and interviews, counseling, and direct practice carried out data collection. The results obtained from this fish feed-making training activity are: 1) the community knows that the actual feed they buy so far ingredients are around them and are very simple, 2) the community is able to absorb the knowledge gained about how to make feed starting with the preparation of tools and materials, making formulations, to making feed and given directly to cultured fish.   Fish farmers can easily make fish feed, and the raw materials used in making feed can be obtained in the surrounding area, making it easier for farmers to make their feed.